Chapter 10 'You don't Need Proof When You've Got Instinct!': Gut Feelings and Some Limits to Parental Authority - Meulen, ter, Ruud (Taylor & Francis, 2015)
This book reflects on the many contributions made in and to European bioethics to date, in various locations, and from various disciplinary perspectives. In so doing, the book advances understanding of the academic and social status of European bioethics as it is being supported and practiced by various disciplines such as philosophy, law, medicine, and the social sciences, applied to a wide range of areas. The European focus offers a valuable counter-balance to an often prominent US understanding of bioethics. The volume is split into four parts. The first contains reflection on bioethics in the past, present and future, and also considers how comparison between countries and disciplines can enrich bioethical discourse. The second looks at bioethics in particular locations and contexts, including: policy, boardrooms and courtrooms; studios and virtual rooms; and society, while the third part explores the translation of theories and concepts of bioethics into the clinical setting. The fourth and final section focuses on academic expressions of bioethics, as it is theorised in various disciplines and also as it is taught, whether in classrooms or at the patient's bedside. The book features unique contributions from a range of experts including: Alastair V Campbell; Ruth Chadwick; Angus Dawson; Raymond G. De Vries; Suzanne Ost; Renzo Pegoraro; Rouven Porz; Paul Schotsmans;Jochen Vollmann; Guy Widdershoven and Hub Zwart.